Direct and indirect effects of silver nanoparticles on freshwater and marine microalgae (Chlamydomonas reinhardtii and Phaeodactylum tricornutum). (July 2017) - Sendra, M.; Yeste, M.P.; Gatica, J.M.; Moreno-Garrido, I.; Blasco, J.
Abstract: The last decade has seen a considerable increase in the use of silver nanoparticles (AgNPs), which are found in many every-day consumer products including textiles, plastics, cosmetics, household sprays and paints. The release of those AgNPs into aquatic environments could be causing ecological damage. In this study we assess the toxicity of AgNPs of different sizes to two species of microalgae, from freshwater and marine environment ( Chlamydomonas reinhardtii and Phaeodactylum tricornutum respectively). Dissolution processes affect the form and concentration of AgNPs in both environments. Dissolution of Ag from AgNPs was around 25 times higher in marine water. Nevertheless, dissolution of AgNPs in both culture media seems to be related to the small size and higher surface area of NPs. In marine water, the main chemical species were AgCl2 − (53.7%) and AgCl3 −2 (45.2%). In contrast, for freshwater, the main chemical species were Ag + (26.7%) and AgCl − (4.3%). The assessment of toxicological responses, specifically growth, cell size, cell complexity, chlorophyll a, reactive oxygen species, cell membrane damage and effective quantum yield of PSII, corroborated the existence of different toxicity mechanisms for microalgae. Indirect effects, notably dissolved Ag ions, seem to control toxicity to freshwater microalgae, whereas direct effects, notably attachment onto the cell surface and the internalization of AgNPs inside cells, seem to determine toxicity to the marine species studied. This research contributes to knowledge on the role of intrinsic and extrinsic factors in determining the behavior of NPs in different aquatic environments and the interaction with microalgae. Graphical abstract: Highlights: Ionic strength and size of AgNPs govern the dissolution process. Toxicity of AgNPs to freshwater microalgae seems to be determined by the presence of Ag + in culture media (indirect effect). Toxicity of AgNPs in marine microalgae seems to be ruled by direct effects of AgNPs, as adsorption and internalization.